2020
DOI: 10.4149/neo_2019_190131n94
|View full text |Cite
|
Sign up to set email alerts
|

Second-generation Src/Abl inhibitor bosutinib effectively induces apoptosis in human esophageal squamous cell carcinoma (ESCC) cells via inhibiting Src/Abl signaling

Abstract: Esophageal cancer is a prevalent type of cancer worldwide and is ranked sixth among cancer-associated mortalities. Aberrant activation of the non-receptor tyrosine kinase Src and c-Abl contribute to the progression of ESCC. Thus, targeting these kinases to treat ESCC is a promising strategy. In this paper, we report that the potent dual Src/Abl inhibitor bosutinib exerts anti-tumor effects on ESCC. Bosutinib inhibits ESCC cell proliferation in a dose-dependent manner. Furthermore, bosutinib suppresses the colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Based on the bioinformatics-based screening and validations using both in vitro and in vivo models, we revealed a notable association between high UPP1 expression and increased sensitivity to Bosutinib and Dasatinib. Bosutinib is a selective inhibitor designed to target the Src family kinases and has been approved for the treatment of chronic myeloid leukemia (CML) in adults 74,75 . Dasatinib, on the other hand, has a broader range, inhibiting not just the Src family kinases but also several other kinases 76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the bioinformatics-based screening and validations using both in vitro and in vivo models, we revealed a notable association between high UPP1 expression and increased sensitivity to Bosutinib and Dasatinib. Bosutinib is a selective inhibitor designed to target the Src family kinases and has been approved for the treatment of chronic myeloid leukemia (CML) in adults 74,75 . Dasatinib, on the other hand, has a broader range, inhibiting not just the Src family kinases but also several other kinases 76,77 .…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib enhances cisplatin sensitivity in ESCC cells via suppression of the PI3K/AKT and Stat3 pathways ( Chen et al, 2015 ). Bosutinib effectively induces apoptosis in ESCC cells by inhibiting Src/Abl signaling ( Ha et al, 2020 ). In our present study, we demonstrated SRC was overexpressed in ESCC tissues compared with normal esophageal mucosa.…”
Section: Discussionmentioning
confidence: 99%